The Effect of Organic and Inorganic Fertilizers on the Growth Performance of Date Palm Offshoots - Hamza AL-Alwani, Haderr Abd-Alkadhim (American Journal of Biology and Natural Sciences, 2026)
The date palm, Phoenix dactyl lifera is an important fruit crop of the tropics and subtropics. Date palm propagation is offshoot dependent, which needs several environmental factors resemble the natural conditions for achieving successful establishment and long-term productivity. Fertilization is crucial for the vegetative and root growth of the offshoots. Nowadays, organic-, inorganic-fertilizer and their combinations are considered to be interesting to promote the growth of the offshoot and to improve soil fertility. Organic fertilizers, including compost and manure, release key nutrients slowly while improving soil structure and increasing microbial activity and can be used in a manner that is biologically, environmentally, and economically sustainable. On the other hand, inorganic fertilizers contain nutrients such as N, P and K that are directly available and facilitate fast vegetative growth, but they may cause environmental pollution and soil degradation when they are used excessively. The combination of organic and inorganic fertilizers is regarded as an effective approach to balance between speed of plant growth and improvement of soil structure. The objective of this research was to assess the impact of organic, inorganic and integrated (organic + inorganic) fertilizers on growth of date palm offshoots in the nursery. The test consisted of four treatments (control, i.e. without fertilizer, inorganic fertilizer, organic fertilizer and a mix of organic and inorastic fertilizer) and each treatment was repeated 3 times. Important parameters to be recorded in growth were onshoot height, number of leaves, leaf diameter, chlorophyll content of leaves, and dry matter of the vegetative parts within a 12-month period. Results showed that offshoots receiving treatment of a mixed application of the organic and the inorganic fertilizers had the best growth performance in terms of height, number of leaves, chlorophyll content, and dry matter accumulation. Organic fertilizers also exhibited better growth parameters when compared to control; however, inorganic fertilizer significantly improved early vegetative growth but limited in improving long-term soil fertility and crop growth. The investigation was aware of the fact that organic and inorganic blended sources of fertilization for the offshoots of date palm hold best prospects for the sustainable development of the same. These results offer useful advice for nursery practices and sustainable date palm production and reiterate the need to balance both growth and environmental costs of implementing chemical fertilizers. Long term studies are also recommended to assess the impact of different fertilization regimes on the field performance and yields of mature date palms.